Representasi Makna Gaya Kepemimpinan Otoriter Tokoh Thomas Shelby dalam Film Serial Peaky Blinders - Mochammad Fajar Adityansyah; Dede Lilis Chaerowati (Bandung Conference Series: Communication Management, 2023)
Abstract. A leader usually has a communication style that is quite interesting and unique according to his own leadership style. Leadership is a person's ability to influence other people to do something with the goals to be achieved. There is one character in a serial film called 'Peaky Blinders' that fulfills the criteria of being a leader as it should be, that character is Thomas Shelby. This study is entitled "Representation of the Meaning of Thomas Shelby's Authoritarian Leadership Style in Peaky Blinders Serial Film". The purpose of this research is to find out the denotation, connotation, and mythical meaning of Thomas Shelby's leadership in the Peaky Blinders series. The research method used in this study is a qualitative method with Roland Barthes's semiotic. Data collection techniques used in this research are observation, documentation and literature study. The data analysis technique in this study is to use semiotic analysis from Roland Barthes' theory. In Roland Barthes' theory, researchers will analyze data taken from the movie "Peaky Blinders". The researcher will see how the authoritarian leadership style of Thomas Shelby is. Based on the results of research on the meaning of denotation, Thomas Shelby has a separate policy that must be followed by all its members. The connotation meaning of Thomas Shelby's authoritarian leadership style is not always negative, there is also a positive impact on its members, besides that Thomas Shelby is very capable of using his power to influence the behavior of his members, and the meaning of myth in Thomas Shelby's authoritarian leadership style means that Thomas Shelby as a powerful leader in any case. Abstrak. Seorang pemimpin memiliki gaya berkomunikasi yang cukup menarik dan unik sesuai dengan gaya kepemimpinannya sendiri. Kepemimpinan adalah kemampuan seseorang untuk mempengaruhi orang lain agar melakukan sesuatu dengan tujuan yang ingin dicapai. Ada salah satu tokoh di film serial ‘Peaky Blinders’ yang memenuhi kriteria sebagai pemimpin sebagaimana mestinya, tokoh itu bernama Thomas Shelby. Penelitian ini berjudul “Representasi Makna Gaya Kepemimpinan Otoriter Thomas Shelby dalam Film Serial Peaky Blinders”. Tujuan penelitian ini adalah untuk mengetahui makna denotasi, konotasi, dan mitos kepemimpinan Thomas Shelby pada film serial Peaky Blinders. Metode penelitian yang digunakan dalam penelitian ini adalah metode kualitatif dengan pendekatan analisis semiotika Roland Barthes. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah observasi, dokumentasi dan studi pustaka. Teknik analisis data dalam penelitian ini adalah menggunakan analisis semiotika dari teori Roland Barthes. Dalam teori Roland Barthes ini, peneliti menganalisis data yang diambil dari film “Peaky Blinders”. Penulis menganalisis gaya kepemimpinan otoriter dari Thomas Shelby. Hasil penelitian ini makna denotasi, Thomas Shelby memiliki kebijakan tersendiri yang harus diikuti oleh seluruh anggotanya. Makna konotasi gaya kepemimpinan otoriter Thomas Shelby tidak selalu negatif, terdapat dampak yang positif juga untuk anggotanya. Thomas Shelby sangat mampu menggunakan kekuasaannya unutk memengaruhi tingkah laku anggota nya, dan makna mitos dalam gaya kepemimpinan otoriter Thomas Shelby memiliki makna bahwa Thomas Shelby sebagai seorang pemimpin yang berkuasa dalam hal apapun.